TiO2 and ZnO loaded fly ash catalysts - Tuncel, Duygu. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
In this study, two binary catalysts TiO2 supported fly ash (TiO2-FA) and ZnO supported fly ash (ZnO-FA) were sythesized by sol-gel and co-precipitation technique. The as-prepared catalysts were characterized by using several analytical methods and their photocatalytic activities were examined for degradation of methyl orange (MO) under UV irradiation. X-ray diffractometer (XRD), scanning electron microscopy (SEM) with energy dispersive X-ray (EDX) and elemental mapping analysis, surface area analyzer (BET) and UV-vis diffuse reflectance spectrometry (UV-vis DRS) were used for the characterization of the catalysts. XRD analysis supplied information about the anatase phase of TiO2 and ZnO crystallite. The particle sizes of TiO2 in the supported catalysts remained almost the same values while ZnO exhibited reduced crystalline sizes on the ZnO-FA catalysts. SEM (EDX) images revealed variations in the surface morphology of the raw FA after loaded with TiO2 or ZnO nanoparticles. The surface area measurements (BET) of the supported catalysts indicated the formation of mesoporous structures. The supported catalysts revealed higher dark adsorption capacities, following pseudo-second order kinetics. Langmuir adsorption isotherm was well fitted to the experimental data obtained in the dark for both supported catalysts. The loading amounts of the TiO2 and ZnO nanoparticles were effective in the photocatalytic degradation experiments and the best performances were obtained in the presence of 40% TiO2-FA and 0.5M ZnO-FA catalysts. The photocatalytic reactions obeyed the pseudo-first-order kinetics by varying the initial concentrations of the MO. Langmuir-Hinshelwood model was also applicable. The repeatability in the photoactivities of the supported catalysts were confirmed by the recycling studies. A mechanism was postulated for MO degradation. The supported catalysts did not show an activity under visible light irradiation.
Keywords: Fly ash.